(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Bronchiolitis is one of the most common respiratory diseases requiring hospitalization. Nebulized epinephrine and salbutamol therapy has been used in different centres with varying results. Objective: The objective of the study was to compare the efficacy of nebulised adrenaline diluted with 3% hypertonic saline with nebulised adrenaline diluted with normal saline in bronchiolitis. Methods: Fifty three infants and young children with bronchiolitis, age ranging from 2 months to 2 years, presenting in the emergency department of Manikganj Sadar Hospital were enrolled in the study. After initial evaluation, patients were randomized to receive either nebulized adrenaline I .5 ml ( 1.5 mg) diluted with 2 ml of3% hypertonic saline (group I) ornebulised adrenaline 1.5 ml (1.5 mg) diluted with 2 ml of normal saline (group II). Patients were evaluated again 30 minutes after nebulization. Results: Twenty eight patients in the group I (hypertonic saline) and twenty five in groupII (normal saline) were included in the study. After nebulization, mean respiratory rate decreased from 63.7 to 48.1 (p<.01), mean clinical severity score decreased from 8.5 to 3.5 (p<.01) and mean oxygen satw·ation increased 94.7% to 96.9% (p<.01) in group I. In group II, mean respiratory rate decreased from 62.4 to 47.4 (p<.01), mean clinical severity score decreased from 7.2 to 4.1 (p<.01) and mean oxygen saturation increased from 94. 7% to 96. 7% (p<.01). Mean respiratory rate decreased by 16 in group I versus 14.8 (p>.05) in group 11, mean clinical severity score decreased by 4.6 in group versus 3 (p<.05) in group, and mean oxygen saturation increased by 2.2% and 1.9% in group and group respectively. Difference in reduction in clinical severity score was statistically significant , though the changes in respiratory rate and oxygen saturation were not statistically significant. Conclusion: The study concluded that both nebulised adrenaline diluted with 3% hypertonic saline and nebulised adrenaline with normal saline are effective in improving respiratory rate, clinical severity score and oxygen saturation in infants with bronchiolitis; and nebulised adrenaline with hypertonic saline is more effective than nebulised adrenaline with normal saline in improving clinical severity score in bronchiolitis.